Return to normal diet following mandibular fractures – how long is long enough?. Issue 9 (November 2021) - Manzie, T.; David, M.C.; Bobinskas, A.
Abstract: Mandibular fractures are a common injury managed by oral and maxillofacial surgeons. Current open reduction and internal fixation (ORIF) treatment strategies are based on Champy's ideal line of osteosynthesis with the use of miniplate and load-sharing fixation techniques. Postoperative instructions for the duration of a soft diet have varied. This prospective, randomised study reviewed the outcomes of a patient led return to diet at 2 weeks and 4 weeks compared with 6 weeks (control group) following an ORIF of mandibular fractures. There was no significant difference in the incidence of complications between a graduated return to diet at 2, 4, or 6 weeks following an ORIF of the mandible, nor was there a difference in the quality of life during the postoperative period. Smoking has a notable risk factor for complications. The findings of this study suggest that strict adherence to a softened diet may not be necessary, and that patients identified at being of low risk of complications may be able to return to a normal diet from as early as two weeks.